02 FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN JAGUNG DI SULAWESI SELATAN - Jurnal Agribis; Maryam Maryam; Arifin Arifin; Mohammad Anwar Sadat (Universitas Muslim Maros, 2021)
Research aims to understand factors that influences demand corn in south sulawesi and to know variable what most dominant impact on demand corn in south sulawesi. This research carried out in regions south sulawesi province about the request of corn and time used for the implementation of research this is more or less six months, from January until June 2017. Data used in this research was secondary data (time series) from year 2000-2015 to the source of data from central bureau of city makassar .The method of analysis the data used in research is regression analysis linear multiple. With using the tools microsoftt excel 2007 and SPSS (statistical product and service solution) version 16. This research result obtained the value of 0,992) r-squared (determination , this means 99,20 percent variable demand can be explained by the independent variable (production, the price of corn and PDRB), the remaining of 0,80 percent described by other variables that are not included in the model .Test results showing that the f count (α : 1 % ), of greater than f table 499,956 (19,43) means that the independent variable (demand ) had have real impact on the production , the price of corn and regional gross domestic product (PDRB). While the most dominant variable demand for corn is production of corn.